Investigation on Combustion Parameters of Palm Biodiesel Operating with a Diesel Engine - M. H. M., Yasin; R., Mamat; A., Aziz; Ahmad Fitri, Yusop; M. H., Ali (Faculty Mechanical Engineering, UMP, 2015)
Biodiesel is a renewable and decomposable fuel which is derived from edible and non-edible oils. It has different properties compared to conventional diesel but can be used directly in diesel engines. Different fuel properties characterise different combustion-phasing parameters such as cyclic variations of Indicated Mean Effective Pressure (IMEP) and maximum pressure (Pmax). In this study, cyclic variations of combustion parameters such as IMEP and Pmax were investigated using a multi-cylinder diesel engine operating with conventional diesel and palm biodiesel. The experiments were conducted using different engine loads; 20, 40, and 60% at a constant engine speed of 2500 rpm. The coefficient of variation (COV) and standard deviation of parameters were used to evaluate the cyclic variations of the combustion phasing parameters for the test fuels at specific engine test conditions. It was observed that palm biodiesel has lower COV IMEP compared to conventional diesel but is higher in COV Pmax at higher engine loads respectively. In addition, palm biodiesel tends to have a higher recurrence for the frequency distribution for maximum pressure. It can be concluded from the study that the fuel properties of palm biodiesel have influenced most of the combustion parameters.